On Evil. - Morton, Adam, 1945- (Thinking in action., 2013)
Evil has long fascinated psychologists, philosophers, novelists and playwrights but remains an incredibly difficult concept to talk about. On Evil is a compelling and at times disturbing tour of the many faces of evil. What is evil, and what makes people do awful things? If we can explain evil, do we explain it away? Can we imagine the mind of a serial killer, or does such evil defy description? Does evil depend on a contrast with good, as religion tells us, or can there be evil for evil's sake?Adam Morton argues that any account of evil must help us understand three things: w.